Paris spp (Liliaceae): a review of its botany, ethnopharmacology, phytochemistry, pharmacological activities, and practical applications - Zhou, Ji; Liao, Binbin; Miao, Julian; Chen, Xubing (Frontiers in Pharmacology, 2025)
Paris spp., as a traditional medicinal plant, are widely used globally due to their diverse therapeutic properties, including clearing heat and detoxifying, reducing swelling and relieving pain, calming the liver and suppressing convulsions. This review summarizes the research progress of Paris species in the fields of ethnopharmacology, phytochemistry, pharmacological effects, and applications in recent years. The study systematically retrieved information related to the keywords “phytochemistry,” “pharmacology,” and “toxicology” from authoritative databases such as CNKI, PubMed, Elsevier, Web of Science, and SpringerLink, using “Paris L.” as a keyword to collect research materials related to this genus. During this process, a total of 431 metabolites were isolated and identified, with steroidal saponins being the most abundant. In addition to their medicinal uses, Paris spp. have also been applied in hair care products, cosmetics, and health products. Despite their demonstrated significant pharmacological activities and potential clinical applications, the field of Paris spp. research still faces several challenges. For example, the specific mechanisms of action against certain diseases are not fully understood, and multiple studies have shown that Paris species’ extracts may cause adverse reactions and even toxicity. Therefore, further in-depth research and systematic evaluation are needed to promote the safe application and clinical translation of Paris spp.